EVALUATION OF FACTORS AFFECTING DELAY IN UJUNG MENTENG FLAT HOUSING PROJECT WORK - CHANDRA PURNOMO ADJIE; GITA PUSPA ARTIANI; INDRIASARI (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2024)
Economic growth in DKI Jakarta has driven significant infrastructure development, from buildings to public transportation, which play a vital role in people's lives. Smooth development will have a big impact, while delays in construction projects can result in losses and conflicts due to deviations from the set schedule and quality. This forces construction companies to develop rapidly and demands effective strategies to overcome problems that cause delays. For example, the Ujung Menteng Flats project which started on December 4, 2019 and aims to target low-income people in Jakarta, experienced a deviation of -0.271% from the plan, which triggered research on the factors causing this delay. Research using the correlation test method shows several main factors causing delays in the Ujung Menteng Flats construction project, including Cost, Tools, Labor, Management, Weather, and Pandemic factors, with a significant correlation level. Cost is the most dominant factor. The study recommends improving financial planning and management to reduce delays and complete projects on budget, as well as improving project management and the availability of tools and labor.